ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI SPLDV DI KELASVIII SMPN 3 MANIAMOLO TAHUN PEMBELAJARAN 2020/2021 - Karolus Sanononi Sarumaha(1); Rohpinus Sarumaha(2); Efrata Gee(3) (Universitas Nias Raya, 2022)
This research is motivated by the importance of having mathematical communication skills in the material of a two-variable linear equation system. This study aims to describe mathematical communication skills and determine the factors that affect the mathematical communication skills of eighth grade students of SMPN 3 Maniamolo on SPLDV material. This research uses qualitative research with descriptive research approach. The informants of this research were students of class VIII of SMPN 3 Maniamolo as many as 37 students. The data were analyzed by the steps of data collection, data reduction, data presentation and drawing conclusions. The research instrument used was a test of students' mathematical communication skills and interviews. The research findings show that: (1) in general, the communication skills of class VIII SMPN 3 Maniamolo students are in the medium category, there are 4 students (10.81%) in the high category, 22 students (59.46%) moderate, and 11 students (29 ,73%) in the low category. The percentage of students' communication skills on each indicator, namely, Written Text (33.00%), Drawing (36.41%), and Mathematical Expressions (14.44%). (2) Factors that influence students' mathematical communication skills are: students' interest in learning mathematics, basic knowledge of mathematics, mastery and understanding of students' concepts of material, activeness of students in learning mathematics and teachers. Through this research, the researcher suggests that students' mathematical communication skills should be further improved by practicing math problems related to mathematical communication.